The Place of Friendship in the Life and Dramatic Work of Louis-Benoît Picard - Al Btoush, Ahmad (Dirasat: Human and Social Sciences, 2022)
Literature has never ceased to shed light on the problems and catastrophes that haunt humanity. Louis-Philippe Dalembert's novel Mur Méditerranée, written in 2019, is no exception to this rule. It is inspired by the tragedy of a clandestine migrant ship that sank in the Mediterranean while sailing to Europe. This authentic human catastrophe deserves to be described, narrated, and analyzed. The Mediterranean Sea which symbolizes openness turns into a place of imprisonment for migrants, a place where the dream of ascending to heaven turns into an infernal fall. This study aims to identify and analyze the novel’s haunting literary images in the light of psychoanalytic criticism and mythocriticism to elicit their symbolic meaning.